2016
DOI: 10.1080/00450618.2016.1194472
|View full text |Cite
|
Sign up to set email alerts
|

The circumstances and characteristics of fatal falls in Victoria, Australia: a descriptive study

Abstract: Falls are the 18th major cause of death in Australia. The intention of this study was to provide a comprehensive understanding of fatal falls in an Australian context through documenting the circumstances of fall-related deaths and investigating the characteristics surrounding those falls. A retrospective review of fatal falls in the state of Victoria from 2005 to 2014 was undertaken using the National Coronial Information System online database. Details recorded for each fatal fall case comprised the circumst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A retrospective review of individuals who died following a fall from height in Victoria, Australia, between 2005 and 2014 was undertaken using the National Coronial Information System (NCIS) online database . Cases which documented the individual's intrinsic variables (i.e., age, sex, body mass index (BMI), psychoactive drug use, and pre‐existing mental/physical conditions) and extrinsic variables (i.e., height fallen, manner of death, and landing surface) were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective review of individuals who died following a fall from height in Victoria, Australia, between 2005 and 2014 was undertaken using the National Coronial Information System (NCIS) online database . Cases which documented the individual's intrinsic variables (i.e., age, sex, body mass index (BMI), psychoactive drug use, and pre‐existing mental/physical conditions) and extrinsic variables (i.e., height fallen, manner of death, and landing surface) were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective review under ethics approval of the NCIS database for fatal falls in the state of Victoria, Australia, between 2005 and 2014 identified 227 cases of low (≤3 m) free falls . Coronial documentation for each of these cases (i.e., pathology report, toxicology report, police report, and the coroner's findings) was reviewed, and the variables that have previously been reported in the literature to influence an individuals' fall , as these influence how their skeleton fractures, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Details of these investigations include the autopsy report, police scene attendance report, postmortem toxicology results, and the coroner's findings, and are recorded in the National Coronial Information System (NCIS) online database. A retrospective review of the NCIS for fatal high free falls between 2005 and 2014 identified 157 cases . This was supplemented with a further 31 cases since 2014 using the Victorian Institute of Forensic Medicine's (VIFM) internal case management system.…”
Section: Methodsmentioning
confidence: 99%